Global report on food crises 2019: Key findings - Technical Discussion - Russo, Luca (2019)
Luca Russo POLICY SEMINAR Technical Discussion on the 2019 Global Report on Food Crises: Working together to prevent food crises Co-Organized by IFPRI, FAO North America and Food Security Information Network (FSIN) APR 26, 2019 - 09:30 AM TO 11:00 AM EDT